EFFECTS OF ARTIFICIAL DIETS CONTAINING DIFFERENT PROTEIN - LEVELS ON GROWTH AND FEED EFFICIENCY OF CATFISH (CLARIAS BATRACHUS L.) - Mollah, M F A; Hossain, M A (Indian Journal of Fisheries, 2011)
Attempt was made to determine the optimum level of dietary protein in formulated feed for catfish, Clariasbalrachus. Five kinds of artificial diets were prepared with laboratory made fishmeal as a single source ofprotein. The level of protein in test diets were maintained at 30,34.7,39.5,44.1 and 48.9 in dry weigh t basis.The growth and feed efficiency of fish fed on 34.7% protein diet was superior to those of the fish fed on 30%protein diet. However, both groups were significantly inferior to 39.5% protein group. On the other hand,no significant differences were recognized among 39.5,44.1 and 48.9% protein diet groups, though slightlyhigher growth and feed efficiency were observed in groups with higher protein levels. These findingsindicate that 39.5% protein is optimum in diet for commercial rearing of catfish, C. batrachus.